Application of Carbon Extraction Replicas in the Microstructural Analysis of High Strength Microalloyed Steels - K. Poorhaydari; B. M. Patchett; D. G. Ivey (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
In this paper, some applications of carbon extraction replicas, as samples for transmission electron microscopy (TEM), are discussed. Modern high strength microalloyed (HSMA) steels, used as structural or pipeline materials, have very small grains with substructures. Replicas used in TEM can resolve the grain boundaries and can be used for grain size measurements in cases where the small size of the grains pushes the resolution of conventional optical microscopes. The grain size variations obtained from replicas correlated very well with mechanical property variations, indicated by hardness, in the fine-grained heat-affected zone and base metal of some welded HSMA steels. Replicas are also very suitable samples for precipitate examination with analytical TEM. Advantages and limitations of the application of replicas, as well as some corrections for the estimation of the volume fraction of fine precipitates, are discussed.